Relationship Analysis and the Enhancement of Student Social Intelligence in Problem-Based Social Science Learning - Fadhil Nur Hidayat; Herwin; Sekar Purbarini Kawuryan; Dhiniaty Gularso; Aminul Qodat (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study seeks to investigate and analyze the relationship between the implementation of Problem-Based Learning (PBL) in Basic Social Sciences education at PGRI University Yogyakarta and the improvement of students' social intelligence. The study employs a qualitative approach with a case study design, in which the researcher conducts interviews and observations with six students and One Lecturer participating in PBL-based Basic Social Sciences education. These individuals are from various regions, and each has unique characteristics. According to the researcher's criteria, the informants are selected as essential informants. The subjects of this study are second-semester student in PGRI University Yogyakarta's Elementary School Teacher Education program. The investigation is conducted over a span of two months, beginning on March 27, 2023 and ending on May 11, 2023. Documentation, in-depth interviews, and participant observation are data collection methods. The findings suggest that the relationship between social intelligence and the implementation of Problem-Based Learning (PBL) in Basic Social Sciences education enables students to develop social skills such as cooperation, effective communication, empathy, and situational understanding, which are essential components of social intelligence. Keywords:  Social Intelligence, Problem-Based Learning (PBL), Social Science